2016
DOI: 10.1021/acs.jchemed.6b00154
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid and 4-Nitroaniline Removal from Water Using Magnetic Biochar: An Environmental and Analytical Experiment for the Undergraduate Laboratory

Abstract: Adsorption studies of salicylic acid (SA) and 4-nitroaniline (4NA) from aqueous solutions were performed with magnetic biochar (MBC) in order to train students in analytical techniques such as standard calibration curves, UV–vis spectrophotometry, and chemical separations within the context of wastewater purification. Analysis of samples purified by MBC enhances student understanding of water quality and the importance of potable water production, a growing worldwide concern. MBC was prepared by iron oxide pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Biochar containing electroactive quinoid functional groups and polycondensed aromatic sheets can act as an electron shuttle to mediate electron-transfer reactions [19,23]. Within this context, several mechanisms can occur on the biochar surface, including redox reactions and donor-acceptor complex formation, with many of these mechanisms being pH dependent [33]. Furthermore, with respect to the sorption properties of biochar, it has been shown that biochar has a strong affinity for PAHs [20,30].…”
Section: Catalytic Activity Of Fe 3 O 4 -Wb With Respect To Pah Reducmentioning
confidence: 99%
“…Biochar containing electroactive quinoid functional groups and polycondensed aromatic sheets can act as an electron shuttle to mediate electron-transfer reactions [19,23]. Within this context, several mechanisms can occur on the biochar surface, including redox reactions and donor-acceptor complex formation, with many of these mechanisms being pH dependent [33]. Furthermore, with respect to the sorption properties of biochar, it has been shown that biochar has a strong affinity for PAHs [20,30].…”
Section: Catalytic Activity Of Fe 3 O 4 -Wb With Respect To Pah Reducmentioning
confidence: 99%
“…Preparation of magnetic biochar -Magnetic biochar was obtained by coprecipitation of Fe(II) and Fe(III) ions on the particles of previously prepared non-magnetic biochar, in alkali medium, following an experimental procedure similar to that proposed by Karunanayake et al [39].…”
Section: Methodsmentioning
confidence: 99%
“…Humins first underwent a thermal treatment previously proposed by Tosi et al [37] in order to get a crosslinked rigid foam. Then, magnetic biochar was obtained by chemical co-precipitation under alkaline conditions [39]. After that, adsorption kinetics and adsorption isotherms were performed by using methylene blue as a pollutant.…”
Section: Magnetic Biocharmentioning
confidence: 99%
“…e pH was raised to 11 by adding 0.05 M NaOH solution, dropwise. After mixing for 60 min, the organic residues were removed by washing with distilled water (H 2 O) until the pH of the washing solution reached 7.0. e fine powdered modified biochar (FMBC) was vacuum-filtered and then dried overnight at 50°C in a hot air oven [18].…”
Section: Biochar Productionmentioning
confidence: 99%